Do Toxoplasma gondii apicoplast proteins have antigenic potential? An in silico study. (February 2020) - Can, Hüseyin; Erkunt Alak, Sedef; Köseoğlu, Ahmet Efe; Döşkaya, Mert; Ün, Cemal
Graphical abstract: Highlights: Apicoplast proteins were first time analyzed to reveal whether its proteins have an antigenic potential. It was found that 19 apicoplast proteins showed antigenic property. 5 proteins were selected as more antigenic due to having a signal peptide or a high antigenicity value. Abstract: Toxoplasma gondii, one of the extensively studied Apicomplexan parasites, is prevalent worldwide in animals and humans. Apart from its nuclear genome, T. gondii contains an apicoplast genome in 35 kb length which is originated from a secondary endosymbiotic event. In this study, we aimed to investigate the antigenic potential of apicoplast genome encoded proteins (n:28) of T. gondii using in silico analysis. For this purpose, proteins were primarily predicted to reveal antigenic probability and then, several bioinformatics analyses were applied for all predicted antigenic apicoplast proteins to analyze physico-chemical parameters, subcellular localization and transmembrane domain. Also, further prediction analyses including structural, B cell and MHC-I/II epitope sites as well as post-translational modifications were performed for antigenic proteins that have a signal peptide or a high antigenicity value. Of the 28 apicoplast proteins, 19 were predicted as probable antigen. Among antigenic proteins, ribosomal protein S5, L11 and S2 were predicted to have signal peptide whereas ribosomal protein L36 and S17 were predicted to have a significantly high antigenicity value ( P < 0.05 ). In addition, ribosomal protein S5, L11, S2, L36 and S17 were predicted to have a lot of epitopes which have low IC50 and percentile rank value indicating a strong binding among epitopes and MHC-I/II alleles, and post-translational modifications such as N-linked glycosylation, acetylation and phosphorylation. To the best of authors' knowledge this is the first study to show the antigenic potential and other properties of apicoplast-derived proteins of T. gondii .